Antenna Solutions for 4G Smartphones in Laser Direct Structuring Technology - Cihangir, Aykut; Sonnerat, Florence; Gianesello, Frederic; Gloria, Daniel; Luxey, Cyril (Společnost pro radioelektronické inženýrství, 2016)
Two antenna designs operating in the LTE/4G cellular frequency bands are proposed in this paper. Both designs consist of a driven strip which capacitively excites a parasitic grounded strip for a better matching response around 700 MHz. The antennas are realized using Laser Direct Structuring (LDS) technology on POCAN plastic material with a height of 5 mm above the system Printed Circuit Board. Passive matching circuits are necessary at each antenna’s feed, to match the input impedance to 50 Ohm at the desired operating bands (700-960 MHz and 1.7-2.2 GHz for the first design and 700-960 MHz and 1.7-2.7 GHz for the second). The simulation results are validated through s-parameter and total efficiency measurements. To form a basis for future studies, the effect of the hand and the head of the user are investigated upon the antenna performance.
Keywords: Mobile antennas; parasitic antennas; LTE; 4G; LDS; matching network